Design and development of an unmanned aerial vehicle to capture real-world illumination for image-based lighting for dense urban environment. Issue 2 (4th March 2018) - Tai, Nan-Ching; Jang, Han-Wei
ABSTRACT: Daylighting not only provides alternative illumination to artificial lighting that can reduce energy consumption, it also can increase an inhabitant's productivity and help to relieve depression. Maximizing the access of daylight for an interior space in a dense urban environment has thus become a priority in lighting design. Digital lighting simulation using high dynamic range imaging for image-based lighting can provide accurate daylight simulation of an interior luminance distribution. However, the method of generating a high-dynamic range light probe image is limited to the setting of a flat landscape with an unobstructed view. This paper presents an innovative system that is implemented using a lightweight smartphone camera equipped with a fish-eye lens on a customized unmanned aerial vehicle (UAV). The system can be remotely controlled to loiter, recording multiple images in a horizontal direction. The captured images can then be assembled into a high dynamic range light probe image to be used as the image-based lighting source for interior spaces with one-directional access to daylight. The pilot test proved that the light probe images generated with the constructed prototype and system provide reasonable accuracy in daylight simulation. GRAPHICAL ABSTRACT: